The Effect Of Use Animation Media On Learning Outcomes In Science Learning Of The Fourth Grade Students Telkom Makassar - Gilang Ramadhan; Rohana Rohana; Amir Pada (International Journal of Elementary School Teacher, 2021)
This research is a quantitative approach with the type of pre-experiment research that aims to determine (1) The description of the application of animation media in class IV A SD Telkom Makassar, (2) The description of the learning outcomes of students in class IV A SD Telkom Makassar, and (3) The effect of the application of animation media on the learning outcomes of students in class IV A SD Telkom Makassar. The independent variable in this study is the application of animation media, while the dependent variable is the learning outcomes of students. The population in this study were all grade IV students of SD Telkom Makassar as many as 83 people, while the sample was class IV A as an experimental class with 29 students with purposive sampling technique. The results of the research conducted can be concluded that (1) The description of animation media in class IV A SD Telkom Makassar took place effectively because the percentage category for each meeting increased. (2) The description of the learning outcomes of students in class IV A SD Telkom Makassar has increased. This is evidenced by the posttest scores of students in the high category after treatment while the pretest scores were in the medium category before treatment. (3) Data on the results of the study were obtained by giving a pre test and post test in the form of a multiple choice test. Based on the results of inferential statistical analysis obtained Sig. (2-tailed) from the results of the Paired Sample Test of 0.000, this value is smaller than α = 0.05. It can be concluded that animation media has a significant effect on the learning outcomes of class IV A Telkom Makassar students.